2012
DOI: 10.1186/1748-717x-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric consequences of translational and rotational errors in frame-less image-guided radiosurgery

Abstract: BackgroundTo investigate geometric and dosimetric accuracy of frame-less image-guided radiosurgery (IG-RS) for brain metastases.Methods and materialsSingle fraction IG-RS was practiced in 72 patients with 98 brain metastases. Patient positioning and immobilization used either double- (n = 71) or single-layer (n = 27) thermoplastic masks. Pre-treatment set-up errors (n = 98) were evaluated with cone-beam CT (CBCT) based image-guidance (IG) and were corrected in six degrees of freedom without an action level. CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
125
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 35 publications
10
125
0
5
Order By: Relevance
“…Ramakrishna et al [8], Guckenberger et al [9] and Tryggestad et al [29] reported an intrafraction error in the order of 1 mm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ramakrishna et al [8], Guckenberger et al [9] and Tryggestad et al [29] reported an intrafraction error in the order of 1 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Weltens et al [6] assessed the impact of the addition of MR imaging on the interobserver variability of brain tumour delineations. Patient setup and immobilization device accuracy has been studied by for example Meyer et al [7], Ramakrishna et al [8] and Guckenberger et al [9]. http End-to-end tests are used to measure the overall geometrical and dosimetric accuracy of the treatment chain for an ideal patient.…”
mentioning
confidence: 99%
“…Influence of rotational setup errors, which can be identified with systematic G/R deviations, were extensively reported in literature (23)(24)(25). VMAT has been successfully implemented for different treatment sites with tolerance of gantry angle to agreement of 0.5 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a patient may not require repositioning with singleisocenter technique, but accurate setup is critical since both translational and rotational error degrade conformality. 29, 30 At our institution, intrafraction motion after initial setup is minimized by continuous monitoring in real-time with SIG. 20 …”
Section: Discussionmentioning
confidence: 99%